Process-based modelling of the methane balance in periglacial landscapes - Kaiser, Sonja (2017)
A detailed process-based methane module for the global land surface scheme JSBACH has been developed that is general enough to be applied in permafrost regions as well as wetlands outside permafrost areas. Methane production, oxidation and transport by ebullition, diffusion and plants are represented. Oxygen has been explicitly incorporated into diffusion, transport by plants, bulk soil oxidation and rhizospheric oxidation. Permafrost and wetland soils show special behaviour, e.g. variable soil pore space due to freezing/thawing or water table depths due to changing soil water content. This was integrated directly into the methane-related processes. A detailed application at the Samoylov polygonal tundra site, Lena River Delta, was used for evaluation purposes, which shows differences in the importance of the several processes and in the methane dynamics under varying soil moisture, ice and temperature conditions during different seasons and on the two different microsites, the elevated moist polygonal rim and the depressed wet polygonal centre. The evaluation shows sufficiently good agreement with field observations despite the module was not specifically calibrated to these data. In a second step, an enhanced version of JSBACH, including an updated methane module, was used for regional future climate experiments. The changes concern hydrology, carbon decomposition, methane production, order of the transport processes and plant transport. A new transport process was included, the diffusion through snow. The updated model was applied at the larger area of the Lena River Delta. Detailed analyses of soil respiration and methane process fluxes, their spatial distribution as well as changes with time and in the seasonal behaviour are presented. They show the relevance of methane compared to the carbon dioxide fluxes, the pattern of regions with favourable conditions for methane emissions as well as the increase of fluxes and emission season length due to climate change.